Assessment of Learning Evaluation Strategies in Compliance with KMA No. 450/2024: Case Study of Madrasah Ibtidaiyah - Hilda Wahyuni; Muhammad Nasir; Abdul Bashith (Bidayatuna)
This study analyzes the strategies used in implementing learning evaluation at Madrasah Ibtidaiyah based on the Minister of Religious Affairs Decree (KMA) No. 450 of 2024. The research employs a literature review method with a descriptive-analytical approach. The findings reveal that KMA No. 450 of 2024 is a guideline for implementing the independent curriculum in educational institutions under the Ministry of Religious Affairs, integrating Islamic values as a distinctive characteristic of education in madrasahs. The implementation strategy for learning evaluation in Madrasahs, guided by KMA No. 450 of 2024, aligns with the assessment strategies of the independent curriculum, utilizing assessment methods adapted to Madrasah-specific educational values. The types of assessment applied include diagnostic, formative, and summative assessments. Meanwhile, evaluation techniques include observation, performance appraisal, written tests, oral tests, and portfolios through the Project for Strengthening the Profile of Pancasila and Rahmatan lil Alamin Learners (P5-PPRA).